Предмет: Математика,
автор: ReyCherr
помогите решить.
4/4ab-12a - 2/4ab-28a
Приложения:
![](https://files.topotvet.com/i/510/510b496f83bfdc1e28376d477bfe0958.jpg)
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
2 ) 4/( 4ab - 12a ) - 2/( 4ab - 28a ) = 4/[ 4a( b - 3 ) ] - 2/[ 4a( b - 7 ) ] =
= 1/[ a( b - 3 )] - 1/[2a( b - 7 )] = [ 2( b - 7 ) - ( b - 3 ) ]/[2a(b - 3 )(b - 7 )] =
= ( 2b - 14 - b + 3 )/[2a( b - 3 )( b - 7 )] = ( b - 11 )/[2a( b - 3 )( b - 7 )] .
Похожие вопросы
Предмет: Русский язык,
автор: Аюдзава01
Предмет: Английский язык,
автор: Аноним
Предмет: Беларуская мова,
автор: nikita235lad
Предмет: Английский язык,
автор: truba335privetp2eiqg
Предмет: Биология,
автор: Аноним